Perfil clínico e epidemiológico de infecção sistêmica neonatal por Candida spp em um hospital materno infantil de Belém no ano de 2016 - DIAS, Diana Matos (2021)
The systemic fungal infections by Candida spp in neonate is the relevant cause of sepsis at Neonatal Intensive Care Unit (NICU), leading in the past recent decades to a considerable mortality rate in healthcare centers at a global level. The main goal of this study is to evaluate clinic and epidemiologic aspects of this infection in the neonatal population who receive medical assistance from a Hospital Materno Infantil in Belém, during the year of 2016. This is a descriptive, transversal and retrospective study that analyses patient records in the period from January and December of the mentioned year at the NICU of Fundação Santa Casa de Misericórdia do Pará (FSCMPA) considering as eligibility criteria newborn patients admitted in this period who were classified with positive culture of Candida spp in the data base of Hospital Infection Control Committee of FSCMPA. It was included data from 68 cases of candidemia in which 40% of the patients were identified with infection by Candida parapsilosis, 39% by Candida quilliermondii, 17% Candida albicans, 3% with Candida haemulonii, and 1% by Candida spp. The study has shown that the main risk factors, considering the neonate, are the very low weight (35%) and the prematurity (76%). The most frequent clinic sign identified and common to the newborns studied were the hemodynamic instability of (53%), thermal instability (49%) and lethargy (47%), however, the most prevalent one was the respiratory deterioration which was seen in 88% of the cases. Other signs were also found such as apnea, bradycardia, hyperglycemia, hypotension and abdominal distention, but not in similar proportion. Among the risk factors related to the medical assistance to the newborn were identified 94% of the cases with wide range therapy of antimicrobial, the use of mechanical ventilation, the use of central venous catheter, and extended parenteral nutrition; 31% of the neonate studied had been through some type of surgical procedure and 18% were treated with corticoids. The variation of Candida spp species as well the imprecision of the clinical symptoms of the neonatal candidiasis make difficult to diagnose this infection and therefore the early adequate therapy, for this reason the study reinforce the importance of the evaluation of the risk factors predisposing to fungal infections in neonate in the hospital environment in order to improve the necessary handling with the newborns in the health care centers with high rate of candidemia.